A novel nanoporous Fe-doped lithium manganese phosphate material with superior long-term cycling stability for lithium-ion batteries. Issue 27 (11th June 2015) - Zuo, Pengjian; Wang, Liguang; Zhang, Wei; Yin, Geping; Ma, Yulin; Du, Chunyu; Cheng, Xinqun; Gao, Yunzhi
Abstract : LiMn0.8 Fe0.2 PO4 exhibits an ultralong cycling ability exceeding 1000 cycles with a capacity decay of 0.0068 mA h g −1 loss per cycle. Abstract : Here, we prepared LiMn0.8 Fe0.2 PO4 microspheres with an open three-dimensional nanoporous structure by a facile ion-exchange solvothermal method. The micro/nano-structured material exhibits an ultralong cycle life, and retains a reversible capacity of 105 mA h g −1 after 1000 cycles at 5 C, corresponding to the capacity retention of 94.0% and only 0.0068 mA h g −1 loss per cycle.